If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -4(5x + 1) = 3(7 + -5x) + -9 Reorder the terms: 13 + -4(1 + 5x) = 3(7 + -5x) + -9 13 + (1 * -4 + 5x * -4) = 3(7 + -5x) + -9 13 + (-4 + -20x) = 3(7 + -5x) + -9 Combine like terms: 13 + -4 = 9 9 + -20x = 3(7 + -5x) + -9 9 + -20x = (7 * 3 + -5x * 3) + -9 9 + -20x = (21 + -15x) + -9 Reorder the terms: 9 + -20x = 21 + -9 + -15x Combine like terms: 21 + -9 = 12 9 + -20x = 12 + -15x Solving 9 + -20x = 12 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 9 + -20x + 15x = 12 + -15x + 15x Combine like terms: -20x + 15x = -5x 9 + -5x = 12 + -15x + 15x Combine like terms: -15x + 15x = 0 9 + -5x = 12 + 0 9 + -5x = 12 Add '-9' to each side of the equation. 9 + -9 + -5x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = 12 + -9 -5x = 12 + -9 Combine like terms: 12 + -9 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6
| 10k+4K=-14 | | 28-4a=6(2a-2)-24 | | 2(x+8)=2(2x) | | 7w+2w(w+5)=5 | | 7m-5=58-2m | | 20+2y-6y-4x=0 | | 42-p=18 | | 5(2q-1)+15=10q+50 | | 4-p=17 | | 3.75=0.625K | | 20=28+n | | x+2x+3+4=5x+6x+7+8 | | 2n+4=m | | 4r+5=11 | | 13+29=3a-14+2a | | y=2x+3y+1.5 | | 10+N-15=4 | | 3x+9+4x+1=7x+9 | | 3x+9+4x+x=0x+0 | | -12=-8+a | | 5(3x-2)-x=12x+6 | | v/5-16=10 | | 7x+4x-8x-5=7 | | 3x+9+4x+1=4x+6 | | 4(-8-x+5)=-32x-26 | | 8(3)^(x/2) | | (4x-13)(3x-2)=0 | | -(-a)-(-3)=-4 | | 5+4*3=x | | 9x+13x=88 | | 5+4*3= | | X-0.9X=2500 |